Systemic theory, meritocracy and the depoliticization of institutions: thoughts on the normative route of contemporary liberal political theory – an essay - Danner, Leno Francisco; Bavaresco, Agemir; Danner, Fernando (Aufklärung: journal of philosophy, 2018)
In this paper, we criticize the depoliticization of Western modernization by liberal political theories through the correlation between systemic institutional theory and meritocracy, which is based on the idea of strong individualism with regard to the understanding and the legitimation of social evolution, as well as the logical-technical constitution of social systems. Thus, according to liberal political theories, meritocracy defines social stratification and even systemic institutional evolution throughout time, due to the fact that it is the only political possibility from the viewpoint of a technical-logical understanding of social systems, which implies the delegitimation of an inclusive democratic political praxis concerning the structuring and evolution of such social systems. Our central argument is that a proper political comprehension of Western modernization needs to overcome both the technical-logical understanding of institutions and meritocracy as bases for the comprehension and legitimation of political praxis, institutional evolution, political reformism and social rights. The notions of political democracy and social justice, therefore, must be considered through the refusal of systemic theory and of strong individualism – both assumed by contemporary liberal political theories.